2017
DOI: 10.1111/cpr.12412
|View full text |Cite
|
Sign up to set email alerts
|

SOST, an LNGFR target, inhibits the osteogenic differentiation of rat ectomesenchymal stem cells

Abstract: SOST alleviated the osteogenic differentiation of EMSCs, and LNGFR enhanced the osteogenic differentiation of EMSCs by decreasing SOST, suggesting that the LNGFR/SOST pathway may be a novel target for promoting dental tissue regeneration and engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
(103 reference statements)
2
15
0
Order By: Relevance
“…Moreover, micro‐CT and bone microstructural parameters analysis in p75NTR‐knockout mice showed obvious bone loss in both the femur trabecular and cortical bone, implying that the osteogenic potential was remarkably decreased in the absence of p75NTR. These in vivo data confirmed the findings of previous in vitro studies on the effect of p75NTR in mineralization . Mineralization‐related markers such as Runx2, ALP, Col1, BSP, OCN and OPN have been reported to display a positive correlation with p75NTR in rat EMSCs in vitro.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, micro‐CT and bone microstructural parameters analysis in p75NTR‐knockout mice showed obvious bone loss in both the femur trabecular and cortical bone, implying that the osteogenic potential was remarkably decreased in the absence of p75NTR. These in vivo data confirmed the findings of previous in vitro studies on the effect of p75NTR in mineralization . Mineralization‐related markers such as Runx2, ALP, Col1, BSP, OCN and OPN have been reported to display a positive correlation with p75NTR in rat EMSCs in vitro.…”
Section: Discussionsupporting
confidence: 88%
“…12 Moreover, p75NTR has been reported to participate in tooth morphogenesis and dental hard tissue mineralization. [13][14][15][16][17] However, most molecular signatures on the effect of p75NTR in tooth morphogenesis remain to be uncovered, and the elusive mechanism underlying tooth development has severely restricted dental tissue engineering thus far. In this study, p75N-TR ExIII -knockout mice and EMSCs isolated from p75NTR ExIII−/− and p75NTR +/+ male mice were investigated to reveal the exact mechanism of p75NTR in mineralization regulation, contributing to dental tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the reduced bone mass and osteogenic differentiation in p75NTR −/− mice, we focused on embryonic stem cells to reveal the role of p75NTR in regulating craniomaxillofacial development.CNC-derived EMSCs, the progenitor cells of craniofacial hard tissues including the maxilla and mandible, populate the majority of the first branchial arch mesenchyme and play a crucial role in tooth and mandibular morphogenesis 20. In previous studies, we successfully developed rat EMSCs and detected their multi-differentiation abilities 10,37,38. In this study, EMSCs were isolated from WT and p75NTR −/− embryos separately, but derived from the same heterozygous pregnant mice.…”
mentioning
confidence: 99%
“…Mechanism of MSCs osteogenic differentiation is regulated by complex pathways at transcriptional, post-transcriptional and post-translational levels [42,47,48,49,50], and the related osteogenesis signaling pathways, including TGF-β signaling [21], Wnt signaling [51], Hedgehog [52], Notch [53], NF-κappa B signaling [5], Ras [54], and Calcium Signaling [55]. In our study, a total number of 427 differential genes were identified and found to be related to osteogenic development pathways, such as MAPK signaling pathway, p53 signaling pathway (Cell growth and death), calcium signaling pathway and so on.…”
Section: Discussionmentioning
confidence: 99%